2020
DOI: 10.1002/mgg3.1398
|View full text |Cite
|
Sign up to set email alerts
|

Genetic profile of non‐small cell lung cancer (NSCLC): A hospital‐based survey in Jinhua

Abstract: Background We describe the clinical features, genetic profile, and their correlation in NSCLC patients. Methods A total of 256 Chinese patients with NSCLC were enrolled in this study. NGS‐based genomic profiling of major lung cancer‐related genes was performed on formalin‐fixed paraffin‐embedded tumor samples. Results Of 256 patients with NSCLC, 219 were adenocarcinoma and most of them were in the early stage. Among patients, 63.3% patients have more than two gene mutations. By analyzing variant allele frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 49 publications
2
9
0
Order By: Relevance
“…This is consistent with a recent Chinese report which included 1472 patients and found that EGFR mutation rates were not significantly different between younger (≤45 years) and older patients (52.6% vs 52.0%) (22). ALK rearrangements, which have been consistently reported as being more frequent in the young (5,6,15), were not significantly different in our cohort.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is consistent with a recent Chinese report which included 1472 patients and found that EGFR mutation rates were not significantly different between younger (≤45 years) and older patients (52.6% vs 52.0%) (22). ALK rearrangements, which have been consistently reported as being more frequent in the young (5,6,15), were not significantly different in our cohort.…”
Section: Discussionsupporting
confidence: 93%
“…Likewise, it has been reported that lung cancer in the young is enriched for targetable genomic alterations. compared with older patients ( 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…The American Cancer Society lung cancer statistics for 2022 show that approximately 236,740 new cases of lung cancer were diagnosed in the United States alone (117,910 in men and 118,830 in women) and approximately 130,180 people died from lung cancer (68,820 men and 61,360 women) [ 3 ]. In addition to gender and age differences (diagnosed patients are >65 years of age), many environmental, genetic and lifestyle factors are involved in the development of lung cancer ( Figure 1 ) [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. However, more and more scientific studies highlight the extremely important role of genetic changes in the development and progression of this type of cancer [ 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…In non-squamous NSCLC patients, the most identified driver genes are V-Ki-ras2 Kirsten rat sarcoma viral oncogene homolog (KRAS), Epidermal Growth Factor Receptor (EGFR), and Anaplastic Lymphoma kinase (ALK). Novel treatments directed to these alterations (targeted therapy), like tyrosine kinase inhibitors (TKI), have rapidly become the new standard therapeutic approach in face of their high efficacy [10,11]. However, not every tumor possesses an actionable molecular alteration.…”
Section: Introductionmentioning
confidence: 99%